Arts of (dis)placement: City Space and Urban Design in the London of Breaking and Entering - Bird, Lawrence; Luka, Nik (Cinémas)

(untitled) (Cinémas, 2010)
Anthony Minghella’s 2006 film Breaking and Entering frames two views of London focusing on King’s Cross station, one of the city’s key transportation hubs and, like many such centres, a complex site of marginality. To its main protagonist, the architect/urban designer Will Francis (Jude Law), it is a site to be transformed into a model (in several senses) of what London—and the practice of urban design—have to offer the “new” Europe. The viewpoint of the young Kosovan refugee Miro Simiç (Rafi Gavron) is quite different. He sees King’s Cross from the rooftops, which he clambers as a petty burglar by night to break into local offices. His acts of parkour (defined by its practitioners as “the art of displacement”) are central to the film. Miro, the teenaged character, exists in a space of displacement: displaced from his native Sarajevo, and from the streets of London by his status as refugee and thief. The film contrasts these two viewpoints—one which forms space, and one displaced—by citing real and imagined city-building projects in London, and placing them in relationship to the bodies of Will and Miro.